1999
DOI: 10.1111/j.1540-5915.1999.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

The Auditor's Going‐Concern Disclosure as a Self‐Fulfilling Prophecy: A Discrete‐Time Survival Analysis*

Abstract: The question of how an auditor's going-concern disclosure affects a client's future operations has long troubled the auditing profession. In an attempt to provide further understanding of this issue, we introduce Discrete-Time Survival Analysis (DTSA) to examine the aftermath of 23 1 first-time going-concern disclosures on clients' subsequent continuance. DTSA represents a significant refinement over traditional ordinary least squares (OLS) and logistic (LOGIT) regression in that it provides not only a probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 7 publications
1
56
0
4
Order By: Relevance
“…They found no evidence of the self-fulfilling prophecy effect. Louwers et al (1999) found no proof of it either. However, Nogler (1995), using a sample of 157 American companies that received IGCQs from [1983][1984][1985][1986][1987][1988][1989][1990], found that 33% of them were bankrupt later and 30% experienced an organizational restructure such as mergers, liquidation, or dissolution, supporting the idea of the self-fulfilling prophecy effect.…”
Section: The Self-fulfilling Prophecy Effectmentioning
confidence: 89%
See 1 more Smart Citation
“…They found no evidence of the self-fulfilling prophecy effect. Louwers et al (1999) found no proof of it either. However, Nogler (1995), using a sample of 157 American companies that received IGCQs from [1983][1984][1985][1986][1987][1988][1989][1990], found that 33% of them were bankrupt later and 30% experienced an organizational restructure such as mergers, liquidation, or dissolution, supporting the idea of the self-fulfilling prophecy effect.…”
Section: The Self-fulfilling Prophecy Effectmentioning
confidence: 89%
“…First, does the self-fulfilling prophecy effect exist? The evidence has been inconsistent Taffler, 1992, 2001;George et al, 1996;Guiral, 2011;Louwers et al, 1999;Mutchler, 1984;Tucker and Matsumura, 1998;). Disclosed IGCQs accompany complex and unobservable factors.…”
Section: Introductionmentioning
confidence: 99%
“…effect of self-fulfilling prophecy may exist. Louwers (1999) indicated that the IGCO opinion accelerates business failure and thus has impacts on current and potential investors, creditors, suppliers, and customers. Previous studies test the self-fulfilling prophecy by the percentage approach, calculating the ratio of bankrupt IGCO firms to the total IGCO firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, in a sample of 157 American IGCO firms during the years of 1983 to 1990, Nogler (1995) finds a 33% sample declares bankruptcy after the first year of IGCO issued and supports the effect of self-fulfilling prophecy. In addition, in a sample of 210 IGCO American firms during the years of 1984 to 1991, Louwers (1999) states that 38 (18%) firms are bankrupt after the first year of IGCO issued, 17 (8%) firms after the second year. If applying the DTSA (discrete time survival analysis) modeling, it is 27% after the first year and 18% after the second year, which are similar to a 24% after the first year in the study of Citron and Taffer (1992) for a British IGCO sample.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation